The Effectiveness of Gamba Organic Fertilizer on Increasing Growth and Production of Organic Lettuce (Latuca sativa L) as well as its Effect on Production Costs - Migusnawati Migusnawati; Kiki Amelia; Wilna Sari (Department of Agribusiness, Halu Oleo University Jointly with Perhimpunan Ekonomi Pertanian Indonesia - Indonesian Society of Agricultural Economics (PERHEPI/ISAE), 2022)
This study aimed to determine the response of growth and production of lettuce plants to the application of organic Gamba fertilizer and to see the effect on lettuce production costs. This research aims to provide information to the general public, especially farmers, regarding efforts to apply the efficient use of organic fertilizers to the growth and yield of lettuce. This research was carried out by comparing the cultivation of lettuce that was given Gamba organic fertilizer with that which was not given organic fertilizer. The research variables were plant height, leaf quality, number of leaves, and stem weight. The results of the study would be statistically analyzed using the t-test to determine whether the independent variables partially had a significant effect or not on the dependent variable with a significant degree used was 5 %. The results showed that the application of Gamba organic fertilizer significantly differed in plant growth, height, leaf quality, number of leaves and lettuce production. The production of lettuce cultivation with Gamba organic fertilizer treatment reached 13.2 tons/ha; without treatment, it was 10.2 tons/ha. Regarding financial aspects, the income obtained from cultivation using Gamba organic fertilizer was higher than cultivation without treatment, IDR 596,000 and Rp. 469,000, with an R/C ratio of 1.3 and 1.0, this business using Gamba organic fertilizer is feasible to expand.